Chromosome karyotype analysis of cultivate somatic cells of ganjia sheep / Liu Meng, Ding Gongtao and Roziah Kambol - Liu, Meng; Ding, Gongtao; Kambol, Roziah (2016)
Cytogenetics studies in domestic animal are gaining importance because of their genetics and implication in breeding programmes. The present study describes the chromosome number and karyotypic characteristics of Ganjia sheep and comparison between males and females breeds. We adopt the method of cultivating somatic cells, and analyzed the chromosome karyotype of the Ganjia sheep. The result indicates the diploid chromosome of the Gangia sheep is 2n=54, in which 26 pairs of autosomes and a pair of sex chromosome were observed. Result indicates all autosomes are tip silk. The X chromosome was acrocentric and largest except the first three pairs that were metacentric. The Y chromosome was the smallest, biarmed and probably metacentric chromosome.